Engineered exosomes: a promising design platform for overcoming cancer therapy resistance - Zhang, Peng; Chen, Kai; Liu, Weifeng; Niu, Xiaoying; Wang, Xin; Wang, Jiaqiang; Yao, Weitao; Tang, Xiaodong; Tian, Wen (Frontiers in Cell and Developmental Biology, 2025)
Therapeutic resistance is a formidable barrier in cancer treatment, necessitating innovative solutions to enhance drug efficacy. Exosomes, with their unparalleled biocompatibility, low immunogenicity, and robust cargo protection, have emerged as groundbreaking nanocarriers. This review unveils the transformative potential of exosomes in overcoming drug resistance - encompassing chemotherapy, targeted therapy, and immunotherapy - in a wide spectrum of tumors. Through advanced genetic and non-genetic modifications, exosomes can dramatically enhance drug targeting and cytotoxicity, offering unprecedented precision in treatment. We explore state-of-the-art exosome engineering techniques, their revolutionary applications in clinical trials, and their promise as the next Frontier in therapeutic innovation. This comprehensive review aims to capture the cutting-edge developments and future directions of exosome-based therapies, positioning them as a cornerstone of next-generation oncology.